Application of Topsis Method in Decision Support System Selection of Undergraduate Scholarship Recipients - Matanari, Romiana (Jurnal Matematika Dan Ilmu Pengetahuan Alam LLDikti Wilayah 1 (JUMPA), 2021)
The procurement of scholarship programs is one of the efforts made by the government, companies, or foundations to help individuals for the ongoing education that is being pursued, one of which is in the world of education such as STMIK Pelita Nusantara, where the campus is under the auspices of the Democrat Cemerlang Foundation, a foundation that participate in the provision of scholarship programs, both underprivileged scholarships and merit scholarships. In granting scholarships, many things must be considered so that the right decisions are made, namely the best students who meet the requirements and criteria that have been set and are not subjective. so far pthe campus is experiencing difficulties because there are many students who graduate each year while there are many conditions that must be considered, so faster, more precise and accurate steps are needed to help the campus determine students who are eligible to receive the scholarship.In this study, the TOPSIS method will be applied to select undergraduate scholarship recipients. The method was chosen because TOPSIS is a method whose basic concept is that the best alternative is the alternative that has the closest distance from the positive ideal solution and has the farthest distance from the negative ideal solution from the point of view ofgeometrically using Eucledian distance to determine the relative proximity of an alternative to the optimal solution. The results obtained in this study are that the TOPSIS method using 5 criteria can be applied in the selection of undergraduate scholarship recipients, where 2 out of 5 alternatives have the highest score of 0.657659 as well as scholarship recipients.